Mammalian Atg8-family proteins are upstream regulators of the lysosomalsystem by controlling MTOR and TFEB - Kumar, Suresh (Autophagy, 2020)
Macroautophagy/autophagy delivers cytoplasmic cargo to lysosomes for degradation. In yeast, the single Atg8 protein plays a role in the formation of autophagosomes whereas in mammalian cells there are five to seven paralogs, referred to as mammalian Atg8s (mAtg8s: GABARAP, GABARAPL1, GABARAPL2, LC3A, LC3B, LC3B2 and LC3C) with incompletely defined functions. Here we show that a subset of mAtg8s directly control lysosomal biogenesis. This occurs at the level of TFEB, the principal regulator of the lysosomal transcriptional program. mAtg8s promote TFEB’s nuclear translocation in response to stimuli such as starvation. GABARAP interacts directly with TFEB, whereas RNA-Seq analyses reveal that knockout of six genes encoding mAtg8s, or a triple knockout of the genes encoding all GABARAPs, diminishes the TFEB transcriptional program. We furthermore show that GABARAPs in cooperation with other proteins, IRGM, a factor implicated in tuberculosis and Crohn disease, and STX17, are required during starvation for optimal inhibition of MTOR, an upstream kinase of TFEB, and activation of the PPP3/calcineurin phosphatase that dephosphorylates TFEB, thus promoting its nuclear translocation. In conclusion, mAtg8s, IRGM and STX17 control lysosomal biogenesis by their combined or individual effects on MTOR, TFEB, and PPP3/calcineurin, independently of their roles in the formation of autophagosomal membranes. Abbreviations: AMPK: AMP-activated protein kinase; IRGM: immunity related GTPase M; mAtg8s: mammalian Atg8 proteins; MTOR: mechanistic target of rapamycin kinase; PPP3CB: protein phosphatase 3 catalytic subunit beta; RRAGA: Ras related GTP binding A.; STX17: syntaxin 17; ULK1: unc-51 like autophagy activating kinase 1